Evaluation of transfer factor protective efficacy against Tuberculosis in Guinea Pigs: Ekram,A.A. AL-Samarrae , Khalifa A. Khalifa , Noria ,R.S. Mohammed - AL-Samarrae, Ekram A.A. (The Iraqi Journal of Veterinary Medicine, 2005)
Transfer factor has been prepared from sensitized guinea pigs against heatkilled Mycobacterium bovis antigen and protective efficacy were evaluated inguinea pigs that gave 1 ml of transfer factor equivalent 5x108 cell / ml of sensitizedand normal cell donor; then challenged with dose 0.01 mg / animal of virulentMycobacterium bovis, After 40 days of challenge all animals were sacrificied.Histologically: - TFs recipient group showed a mono-nuclear cellsinfiltration’s (Lymphocytes & Macrophages) with a mild emphysema of lungs, andliver showed mononuclear cells ,a small necrotic foci in the lymphocytic organs(spleen & lymph nodes); the kidney showed mononuclear cells in glomeruli andurinary tubules ;While the TFn recipient group were an areas of caseated necroticmaterials surrounded by macrophages &Lymphocytes, congestion of internalorgans (Liver and Spleen) and Sever congestion with hemorrhage of alveoli tissue,sever emphysema & consolidation in lung kidney showed tuberculle foci inglomeruli and around urinary tubules .There were no pathgenomic changes in heart muscles of TFs recipient group whilea mild congestion in TFn recipient group.